Cultural values, attitudes, and democracy promotion in Malawi: how values mediate the effectiveness of donor support for the reform of presidential term limits and family law - Daniel Nowack (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Democratisation as a historical process began in the 19th century and is continuing in the 21st. As one aspect of this, donor countries of the Organisation for Economic Co-operation and Development (OECD) are promoting democratic standards around the globe. Democracy promotion now constitutes a central part of development cooperation between donor and partner countries. A number of scholars, however, argue that the current practice of democracy promotion is inherently flawed. By promoting democracy as a culturally invariant political order, donor countries are glossing over significant cultural differences in other countries and this hampers the successful and effective promotion of democratic institutions. Yet, how cultural differences affect the promotion of democracy is still not sufficiently understood. This Discussion Paper is part of the larger research project “What is Democracy's Value? The Influence of Values on the Effectiveness of Democracy Promotion”, which aims at understanding how societal values and attitudes influence the effectiveness of international democracy promotion in African countries. The project looks at how social values and political attitudes mediate the promotion of democracy in two specific realms: attempts by heads of state to circumvent presidential term limits; and reforms to legislation in the realm of family law and LGBTI (Lesbian, Gay, Bisexual, Transsexual, Intersex) rights. This Discussion Paper focuses on two cases situated in Malawi: the attempt of former president Bakili Muluzi to alter presidential term limits in Malawi in 2002; and the reform of Malawi's family and marriage law in 2015. In both cases, donors engaged in democracy promotion in different ways and to different degrees. In the former case, donor countries and organisations warned the Muluzi government to heed the democratic process and thereby seconded popular attitudes. In the latter, donor countries and organisations played an important role in coordinating and mobilising domestic actors towards the reform of Malawi's family and marriage law. Both cases are analysed using in-depth process tracing investigating how donors took part in the constellations of actors engaged in the reform of either the term limit or the family law. The results of the analysis are fourfold: First, although the supply of organisational resources to domestic actors played an important role in both cases, this was not in itself sufficient to guarantee the success of democracy promotion. Rather the coordination of partner organisations played a crucial role in rendering democracy promotion effective. Second, popular mass attitudes played a crucial role in determining the outcome of the two reform processes analysed here. Third, democracy promotion involving the employment of conditionality instruments was effective when the values of the donors matched those of domestic audiences. Finally, when donors were held in esteem in Malawi this aided the effectiveness of democracy promotion by means of public statements and other appropriateness-focused instruments. However, donor esteem did not trump popular attitudes which emphasises that the effectiveness of democracy promotion is sensitive to the specific issue it addresses. These findings prompt a number of recommendations for donors wishing to promote democracy. First, donors need to assess the space available for intervention on an issue-by-issue basis. Values and attitudes in partner countries cannot simply be generalised across issues but are uniquely linked to certain social and political issues. Where attitudes and values in partner countries do not match the goals of donors, it is necessary for donors to support an open discourse. If, in turn, local attitudes and values do favour donors' goals, domestic civil society actors in partner countries are still in need of support from donors for the purpose of mobilisation and coordination. Furthermore, interventions making use of conditionality seem to necessitate a concurrence of attitudes and values between donor and partner countries.
Keywords: 330; Demokratie und Autokratie; Einstellungen; Werte und Normen